Implementasi Literasi Dan Numerasi Pada Program Kampus Mengajar Angkatan 5 Tahun 2023 Di kelas 5 SDN 1 Labuan Tereng - Ni Komang Pasek Diah Arini (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This research aims to determine the implementation of literacy and numeracy in the campus teaching program for class 5 of 2023 in class 5 of SDN 1 Labuan Tereng. The population used in this research was SDN 1 Labuan Tereng, with a total of 30 students, with the sampling technique used was a saturated sampling technique so that the number of samples used in this research was as large as the existing population. The analysis technique used in this research is descriptive by analyzing the work program. Based on the research results, it shows that the campus teaching program for class 5 of 2023 which was implemented at SDN 1 Labuan Tereng in an effort to increase the literacy and numeracy of students at the school ran smoothly and was successful as seen from the implementation of all the work programs carried out as well as an increase in literacy and numeracy results. From the implementation of the Pre-Test and Post-Test scoring, it shows that in the Literacy test, the Pre-Test score, the percentage of students who answered correctly was 37%, while in the Post-Test, the percentage of students who answered correctly was 47%. This shows that the students' scores increased by 10%.